Pneumomediastinum and Subcutaneous Emphysema in the Neck, Axilla, and Chest Regions in a Patient with Olfactory Neuroblastoma Treated with Chemoradiotherapy - Kesarwani, Radha; Pandey, Seema; Maurya, Anil Kumar; Singh, Virendra (Indian Journal of Medical and Paediatric Oncology, 2018)
Spontaneous pneumomediastinum and subcutaneous emphysema in the neck, axilla, and chest do not commonly occur after neoadjuvant cisplatin/etoposide chemotherapy, followed by radiotherapy, and adjuvant cisplatin/etoposide chemotherapy in patients with olfactory neuroblastoma. There are few case reports of pneumomediastinum induced by and occurring during bleomycin/etoposide/cisplatin chemotherapy in testicular cancer. The present case differs from the previous cases in that our patient developed spontaneous pneumomediastinum and subcutaneous emphysema in the neck, axilla, and chest approximately 2 months after completion of chemoradiotherapy for olfactory neuroblastoma. These conditions may have been treatment induced or caused by breath-holding after forceful inspiration. The latter would have created a massive pressure gradient between the alveoli and surrounding structures, causing alveolar rupture, and subsequent passage of air into the mediastinum and subcutaneous tissue of the neck, axilla, and chest.
Keywords: cisplatin; etoposide; mediastinum; radiotherapy; subcutaneous emphysema